(untitled) (Research, Society and Development, 2021)
This article aims to evaluate the statistical correlation between the use of non-pharmacological methods of pain relief during childbirth and puerperal anxiety at the Maternity, in Aracaju, verifying the frequency of use of these techniques and the level of anxiety of parturients. This is a prospective, cross-sectional study, with a quantitative approach with 810 puerperal women, of all ages, from the 75 municipalities in the state of Sergipe who sought the maternity of the SUS Network of Aracaju. From Sep./2019 to Feb./2020, the researchers collected data from the medical records of postpartum women in the first 48 hours after giving birth, through Informed Consent Form (ICF) or Informed Consent Form (ICF). It was assessed whether the parturient women used non-pharmacological methods of pain relief and the IDATE-Trait and IDATE-State questionnaires were applied to measure anxiety in puerperae. The data collected were statistically analyzed by the program Jasp version 0.12.1. The CEP of Tiradentes University approved the study (opinion: 3.695.763). The study showed a positive relationship (p-value < 0.05) between non-pharmacological methods of pain relief and IDATE-ANXiety (SCORE) and IDATE-STATE (SCORE), in the women with higher anxiety score without using the non-pharmacological methods of pain relief. Statistically based, we conclude that there is a significant relationship between non-pharmacological methods of pain relief and puerperal anxiety.